Reproduction, growth and exploitation rate of chiochio (Psectrogaster rutiloides) in the Ucayali river basin between 2008 to 2012 - Riofrio-Quijandría, José C. (2017)
«Chiochio» (Psectrogaster rutiloides) is one of the 10 representative species in the catches of the commercial fleet of Pucallpa, Peru. The aim of this study was to generate information for the understanding of its biology and fishery. Reproductive aspects (time of reproduction, size at maturity [TPM], sex ratio), relationship Length-Weight, growth and rate of exploitation were studied in chiochio landed in Pucallpa ports between 2008 and 2012. Data of length frequency distribution were used to estimate the proportion of individuals below the estimated landed TPM. Also, information from 2011 was used to determine the growth parameters (Loe, K and t0), natural mortality (M) for fishing (F) and total (Z), and estimate the exploitation rate (E). The results showed that «chiochio» spawns during the transition to increasing, and reaches the TPM at 1 year of age with 12.2 cm total length (LT). The Length-Weight equation was different in males and females in 4 of the 5 five analyzed years (p<0.05). Growth parameters of von Bertalanffy equation were Loe=22.58 cm, K=0.66 yr-1, t0=-0.26, M=1.45 yr-1, F=1.73 years-1, Z=3.18 years-1. The exploitation rate was E=0.54, indicating that «chiochio» was in phase of optimal exploitation but requires control actions on landing sizes due to the presence of recruits